Comparison of a Supraglottic Gel Device and an Endotracheal Tube in Keratoplasty Performed Under General Anesthesia: A Randomized Clinical Trial. Issue 1 (January 2016) - Guerrier, Gilles; Boutboul, David; Rondet, Sylvie; Hallal, Dalila; Levy, Jacques; Sjögren, Lea; Legeais, Jean-Marc; Nicolau, Romain; Mehanna, Chadi; Bourges, Jean-Louis; Samama, Charles Marc
Abstract : Purpose: To assess the safety of a laryngeal mask (i-gel) in keratoplasty performed under general anesthesia. Methods: Patients with indications for keratoplasty (n = 110) were enrolled in a prospective study and randomly assigned to the i-gel (n = 55; 30 lamellar keratoplasty and 25 penetrating keratoplasty) or tracheal tube group (n = 55; 29 lamellar keratoplasty and 26 penetrating keratoplasty). Perioperative complications and the recovery time were compared between the 2 groups using the t test or χ 2 test. Contraindications to elective use of the laryngeal mask airway (esophageal reflux, extreme obesity, oropharyngeal pathology, or expected difficult intubation) and expected difficult intubation were excluded. Results: No surgical perioperative complications were reported in either group. There was a significantly greater incidence of coughing at extubation and/or after extubation in the tracheal group (40/55; 73%) than in the laryngeal mask group (3/55; 5%) ( P < 0.001). The recovery time was shorter in the i-gel group (80 minutes; 95% confidence interval, 75–86) compared with that in the tracheal tube group (88 minutes; 95% confidence interval, 82–95) ( P = 0.03). There were no significant differences in the incidence of sore throat and hoarseness between both devices. Conclusions: The use of i-gel for keratoplasty under general anesthesia appears to be safe, reduces the risk of potential ocular hypertension during recovery, and saves recovery time.